2013
DOI: 10.1002/ep.11880
|View full text |Cite
|
Sign up to set email alerts
|

Properties of concrete made with recycled coarse aggregate from waste brick

Abstract: Demolition of old buildings has produced a large amount of waste material. In this paper, experiments were performed to design the mix proportion of concrete made with recycled coarse aggregate from waste brick, and the workability, mechanical performance, and durability of the concrete with different contents of recycled coarse aggregate have also been investigated. Waste brick was used to replace natural aggregate after being treated, called recycled coarse aggregate (RA). Furthermore, fly ash was used as 0,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 18 publications
0
27
0
1
Order By: Relevance
“…12,13 With the limited landfill areas in many parts of the world, there is a need to encounter the feasibility use of concrete production waste as innovative construction materials. Many researches have shown that recycled aggregate from recycled concrete aggregate (RC), [14][15][16] recycled mortar aggregate, 17 recycled concrete block aggregate (RB), 18 recycled crushed clay brick aggregate, 12,19 recycled lightweight concrete aggregate, 20,21 and recycled civil engineering waste aggregate 2 can be used to fabricate Portland cement composites.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 With the limited landfill areas in many parts of the world, there is a need to encounter the feasibility use of concrete production waste as innovative construction materials. Many researches have shown that recycled aggregate from recycled concrete aggregate (RC), [14][15][16] recycled mortar aggregate, 17 recycled concrete block aggregate (RB), 18 recycled crushed clay brick aggregate, 12,19 recycled lightweight concrete aggregate, 20,21 and recycled civil engineering waste aggregate 2 can be used to fabricate Portland cement composites.…”
Section: Introductionmentioning
confidence: 99%
“…Germany first produced concrete products using crushed clay bricks in 1860, but it was not until the end of the Second World War where crushed bricks were used in large quantities as aggregates to produce fresh concrete [3]. According to the literature, the utilization and research of recycled clay bricks are mainly embodied in the following aspects: (1) the influence of the recycled clay brick aggregates completely or partially replacing the natural aggregates on the mechanical properties and durability of recycled concrete [4][5][6][7][8][9][10][11][12]; (2) the influence of recycled clay brick powder as part of cement substitute material on the mechanical properties and durability of concrete and mortar [11,[13][14][15][16]; and (3) the application of recycled aggregates in subgrade and pavement base or subbase filling [17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang and Zong (2013) also confirm the value of water absorption of 16.58%. For comparison, the value of NA is about 1.45% [ 17 ]. Another study reported a coefficient of water absorption of 15.5% to 18.3% depending on the grain size of the RBA [ 18 ].…”
Section: Introductionmentioning
confidence: 99%